Value-added service investment strategy of a two-sided platform with the negative intra-group network externality. Issue 5 (8th May 2018) - Dou, Guowei; Lin, Xudong; Xu, Xiaoping
Abstract : Purpose: Considering the resource constraint, this paper aims to study how to make value-added service (VAS) investment strategy considering the negative intra-group network externality on the seller side from the perspective of a two-sided platform. Design/methodology/approach: The authors use the dynamic game theory, optimization, sensitive analysis and numerical study in this research. The authors model their research question from the perspective of the dynamic game theory, and through optimizing the platform's profit function, the equilibrium results in terms of VAS investing and pricing strategies are derived. To explore the characteristics of the optimal strategies, sensitive analysis is used, and numerical studies are conducted to further illustrate the analytical results. Findings: It is found that the intra-group network externality is not necessarily the determinant for VAS investment strategy, and its overall negative impact can be overtaken by the investment in certain conditions. The optimal VAS investment level decreases in the negative intra-group network externality. Though the VAS investment is on the seller side, it has either positive or negative impact on the pricing for buyers. Moreover, for a stronger intra-group network externality among sellers, the two-sided prices could either increase or decrease. Research limitations/implications: The authors implicate how the intra-group network externality reduces the investment benefit and impacts the other side users. The limitation of considering the intra-group network externalities on only one side needs further extension. Practical implications: The authors provide insights for platform operators in how to use recourse to improve users' utility and how to price the two sides when competition exists on the seller side. Originality/value: This study specifies the role of negative intra-group network externality in determining the investment and pricing strategy of a two-sided platform in addition to the positive inter-group network externality.